Preparation method of silicon-carbon composite material and lithium ion battery containing composite material
By preparing petroleum coke porous carbon and performing vapor deposition doping, secondary granulation and passivation treatment, silicon-carbon composite materials are formed, which solves the problem of poor rate performance and high temperature storage performance of new silicon-carbon materials in lithium-ion batteries, and achieves the high specific surface area, high conductivity and high tap density of the material.
Patent Information
- Application Number
- CN202411958058.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-18
AI Technical Summary
The new silicon carbon material has poor rate performance and high-temperature storage performance in lithium-ion batteries, mainly due to the low electronic conductivity and many structural defects of porous carbon.
By preparing petroleum coke porous carbon, vapor deposition doping is performed in the fluidized bed, then mixing with liquid carbon material for secondary granulation, and finally passing through the process to form a silicon-carbon composite material. This method utilizes the high opposite-element and strength of petroleum coke matrix to reduce impedance and increase compaction density, and improves electron conductivity and coating integrity through heteroatom doping and passivation.
The rate performance and high-temperature storage performance of silicon-carbon composite materials are significantly improved, and the structural stability and cycling performance of the material are enhanced.
Smart Images

Figure CN119852356A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a method for preparing a silicon-carbon composite material and a lithium-ion battery comprising the composite material. Background Art
[0002] Silicon-carbon materials are used in high-energy-density lithium-ion batteries due to their high energy density and wide range of material sources. According to the preparation method, silicon-carbon materials are divided into silane cracking silicon-carbon (referred to as new silicon-carbon) and sand-milling silicon-carbon. The new silicon-carbon has become the preferred material for silicon-based materials used in power batteries due to its high specific capacity, low expansion, and good cycle performance.
[0003] However, the raw materials for preparing the new silicon-carbon material are composed of porous carbon and its deposited nano-silicon. The porous carbon itself has poor electronic conductivity and many porous structural defects in the inner core, resulting in slightly poor rate performance and high-temperature storage of the material. Summary of the invention
[0004] Based on this, the embodiments of the present application provide a method for preparing a silicon-carbon composite material and a lithium-ion battery comprising the composite material, which utilizes the high anisotropy and high strength of the petroleum coke matrix to reduce impedance and increase compaction density, reduces expansion through secondary granulation, improves cycle performance and reduces gas production, and increases the electronic conductivity and coating integrity of the silicon-carbon composite material through passivation, thereby improving the rate performance and high-temperature storage of the silicon-carbon composite material.
[0005] The first aspect of the present application provides a method for preparing a silicon-carbon composite material, the preparation method comprising:
[0006] Preparation of petroleum coke porous carbon;
[0007] Under a protective atmosphere, vapor-depositing and doping the petroleum coke porous carbon in a fluidized bed to obtain an intermediate material;
[0008] The intermediate material is mixed with the liquid carbon material and then transferred to a rotary kiln for secondary granulation treatment;
[0009] The material after the secondary granulation is passivated to obtain a silicon-carbon composite material.
[0010] Furthermore, the preparation of petroleum coke porous carbon comprises:
[0011] Mixing petroleum coke, a pore-forming agent and a cross-linking agent to obtain a mixed material;
[0012] performing a cross-linking reaction on the mixed material;
[0013] The mixed material after the cross-linking reaction is subjected to a first activation reaction to obtain the petroleum coke porous carbon.
[0014] Furthermore, the mass ratio of the petroleum coke, the pore-forming agent and the cross-linking agent is 100:(1-5):
[0015] (5~15);
[0016] The cross-linking reaction comprises: heating the mixed material to 300-500° C. and performing a cross-linking reaction for 1-6 hours;
[0017] The first activation reaction comprises: heating the mixed material after the cross-linking reaction to 1200-1500° C. and introducing carbon dioxide gas at a flow rate of 10-100 ml / min for activation for 30-300 minutes.
[0018] Furthermore, the method comprises using any one or more combinations of the following:
[0019] The pore former is any one of polyamide, polycaprolactam, polyethylene polyamine, polyethylene amine and polycaprolactam; or
[0020] The crosslinking agent is any one of hexanediol diacrylate, triallyl isocyanurate, trimethylolpropane triacrylate and pentaerythritol triacrylate.
[0021] Further, the petroleum coke porous carbon is subjected to vapor deposition doping in a fluidized bed to obtain an intermediate material, comprising:
[0022] performing a second activation reaction on the petroleum coke porous carbon in a fluidized bed;
[0023] The petroleum coke porous carbon after activation reaction is subjected to gas phase nano-deposition;
[0024] The deposited petroleum coke porous carbon is doped with heteroatoms to obtain the intermediate material.
[0025] Furthermore, the second activation reaction comprises: heating the petroleum coke porous carbon to 900-1200° C. and introducing activation gas at a flow rate of 100-500 ml / min for 1-3 hours;
[0026] The gas phase nano deposition comprises: cooling the petroleum coke porous carbon after the activation reaction to 450-650° C., maintaining the pressure of the fluidized bed chamber at 0.1-0.5 MPa, and introducing a chlorosilane mixed gas at a flow rate of 10-50 ml / min for deposition for 60-600 min;
[0027] The heteroatom doping comprises: heating the deposited petroleum coke porous carbon to 800-1100° C., and introducing heteroatom gas for doping at a flow rate of 10-50 ml / min for 30-300 min;
[0028] The heteroatom gas is one of hydrides containing nitrogen, boron, phosphorus, and sulfur, oxides containing nitrogen, boron, phosphorus, and sulfur, and ammonia;
[0029] The chlorosilane mixed gas is a mixed gas of chlorosilane and nitrogen, and the volume ratio of the chlorosilane to the nitrogen is (1-5):10;
[0030] The chlorosilane is one of trichlorosilane, dimethylchlorosilane, hexachlorodisilane, diethyldichlorosilane, dichlorosilane and dichloromethylsilane.
[0031] Furthermore, the mass ratio of the intermediate material to the liquid carbon material is 100:(5-10);
[0032] The secondary granulation treatment includes: carbonization granulation at a temperature of 500 to 800° C. for 1 to 3 hours;
[0033] The liquid carbon material is one of liquid asphalt, liquid epoxy resin, liquid polyurethane resin and liquid polyester resin.
[0034] Furthermore, the passivation treatment of the secondary granulated material to obtain the silicon-carbon composite material comprises:
[0035] The material after secondary granulation is heated to 1000-1500° C., and a passivation gas is introduced at a flow rate of 10-50 ml / min for passivation for 1-6 hours to obtain the silicon-carbon composite material.
[0036] Furthermore, the passivation gas is one of carbon tetrafluoride, carbon difluoride, carbon tetrachloride and carbon dichloride.
[0037] The second aspect of the present application provides a lithium-ion battery, which includes a positive electrode, a negative electrode, an electrolyte, and a separator arranged between the positive electrode and the negative electrode, and the negative electrode includes a silicon-carbon composite material prepared by the preparation method of the silicon-carbon composite material according to any one of the first aspects above.
[0038] The preparation method of the silicon-carbon composite material in the embodiment of the present application and the lithium-ion battery containing the composite material are as follows: preparing petroleum coke porous carbon; vapor deposition and doping the petroleum coke porous carbon in a fluidized bed under a protective atmosphere to obtain an intermediate material; mixing the intermediate material with a liquid carbon material and transferring the mixed material to a rotary kiln for secondary granulation treatment; passivating the material after the secondary granulation to obtain a silicon-carbon composite material. The present application utilizes the high anisotropy and high strength of the petroleum coke matrix to reduce impedance and increase compaction density, thereby obtaining porous carbon with high specific surface area, high conductivity, and high tap density; vapor deposition doping is carried out under a protective atmosphere to effectively introduce heteroatoms on the surface of the petroleum coke porous carbon, thereby improving the surface properties or electronic structure of the silicon-carbon-rich deteriorated material to improve conductivity and enhance structural stability; by mixing the liquid carbon material with the intermediate material and performing secondary granulation, the expansion is reduced, the cycle performance is improved, and the gas production is reduced, thereby improving the first efficiency and rate performance of the battery; and by passivation, a protective film is formed on its surface, such as depositing amorphous carbon, reducing surface states, reducing defects, improving the electrical properties of the carbon-silicon composite material, and improving the electronic conductivity and coating integrity of the silicon-carbon composite material, thereby improving high-temperature storage performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 1 is a schematic flow chart of a method for preparing a silicon-carbon composite material provided in an embodiment of the present application;
[0041] Figure 2 This is a SEM image of the silicon-carbon composite material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other in the absence of conflict. The present invention will be described in detail below in conjunction with the embodiments.
[0043] The embodiments of the present application provide a method for preparing a silicon-carbon composite material, comprising preparing porous carbon from petroleum coke; performing vapor deposition and doping on the porous carbon from petroleum coke in a fluidized bed under a protective atmosphere to obtain an intermediate material; mixing the intermediate material with a liquid carbon material and transferring the mixed material to a rotary kiln for secondary granulation; and passivating the material after the secondary granulation to obtain a silicon-carbon composite material.
[0044] The present application utilizes the high anisotropy and high strength of the petroleum coke matrix to reduce impedance and increase compaction density, thereby obtaining porous carbon with high specific surface area, high conductivity, and high tap density; vapor deposition doping is carried out under a protective atmosphere to effectively introduce heteroatoms on the surface of the petroleum coke porous carbon, thereby improving the surface properties or electronic structure of the silicon-carbon-rich deteriorated material to improve conductivity and enhance structural stability; by mixing liquid carbon materials with intermediate materials and performing secondary granulation, expansion is reduced, cycle performance is improved, gas production is reduced, and the first efficiency and rate performance of the battery are improved; and a protective film is formed on its surface through passivation, such as depositing amorphous carbon, reducing surface states, reducing defects, improving the electrical properties of carbon-silicon composites, and improving the electronic conductivity and coating integrity of silicon-carbon composites, thereby improving high-temperature storage performance.
[0045] See also Figure 1 , which is a schematic flow chart of a method for preparing a silicon-carbon composite material provided in an embodiment of the present application. The method for preparing the silicon-carbon composite material comprises the following steps.
[0046] S1, preparation of petroleum coke porous carbon.
[0047] Petroleum coke porous carbon was prepared by using petroleum coke as a carbon source through chemical pre-oxidation, potassium hydroxide activation and chemical post-oxidation. The petroleum coke porous carbon has high specific surface area, high conductivity, high tap density, stable capacitance performance, and is beneficial to improving the high temperature storage performance of silicon-carbon composite materials.
[0048] In a preferred embodiment, the preparation of petroleum coke porous carbon comprises:
[0049] The petroleum coke, pore-forming agent and cross-linking agent are mixed to obtain a mixed material; the mixed material is subjected to a cross-linking reaction; and the mixed material after the cross-linking reaction is subjected to a first activation reaction to obtain the petroleum coke porous carbon.
[0050] The petroleum coke, pore former and its cross-linking agent are uniformly mixed and carbonized, and the nanometer and micrometer holes left after the carbonization of the pore former are used to realize pore formation, and the cross-linking agent is used to connect the carbon obtained after the carbonization of the petroleum coke, so as to improve the strength of the porous carbon itself, improve the compressive capacity and reduce the expansion. The petroleum coke porous carbon is prepared by high-temperature sintering under the conditions of modified gas (such as carbon dioxide gas), which has the advantages of large pore volume, few defects of carbon-based materials, high compaction density, etc., and improves the specific surface area and porosity of silicon-carbon composite materials, which is conducive to improving the high-temperature storage performance of silicon-carbon composite materials, and the selected petroleum coke raw materials are widely available, low cost and good consistency.
[0051] In a preferred embodiment, the mass ratio of the petroleum coke, the pore former and the cross-linking agent is 100:(1-5):(5-15). The mass ratio of the petroleum coke, the pore former and the cross-linking agent includes but is not limited to the above range, and limiting it within the above range is conducive to improving material utilization, improving the pore structure, electrochemical properties, capacitance characteristics and structural stability of the petroleum coke porous carbon.
[0052] Preferably, the cross-linking reaction comprises: heating the mixed material to 300-500°C and cross-linking for 1-6 hours. The temperature and time during the cross-linking reaction include but are not limited to the above ranges. Limiting it to the above ranges is conducive to the cross-linking agent to fully connect the carbon obtained after carbonization of petroleum coke, thereby optimizing the structure and performance of petroleum tar porous carbon, which is conducive to improving the high temperature storage performance and rate performance of silicon-carbon composite materials.
[0053] Preferably, the first activation reaction comprises: heating the mixed material after the cross-linking reaction to 1200-1500°C and introducing carbon dioxide gas at a flow rate of 10-100 ml / min for activation for 30-300 minutes. The temperature, flow rate and time during the activation reaction at this stage include but are not limited to the above ranges, which are limited to the above ranges. Limiting them to the above ranges is conducive to the full reaction of the material and improving the performance of the petroleum coke porous carbon.
[0054] In a preferred embodiment, the method comprises using any one or more combinations of:
[0055] The pore former is any one of polyamide, polycaprolactam, polyethylene polyamine, polyethylene amine and polycaprolactam; or
[0056] The crosslinking agent is any one of hexanediol diacrylate, triallyl isocyanurate, trimethylolpropane triacrylate and pentaerythritol triacrylate.
[0057] S2, in a protective atmosphere, vapor-depositing and doping the petroleum coke porous carbon in a fluidized bed to obtain an intermediate material.
[0058] The protective atmosphere may be an inert gas atmosphere. Preferably, the petroleum coke porous carbon is transferred to a fluidized bed cavity, and an inert gas is introduced therein to exhaust the cavity air.
[0059] Chlorosilane is cracked through high-temperature cracking to generate nano-silicon, which is deposited in porous carbon to increase the specific capacity. Heteroatoms are coated on its surface to increase the electronic conductivity of the material and improve the rate performance.
[0060] In a preferred embodiment, the petroleum coke porous carbon is subjected to vapor deposition doping in a fluidized bed to obtain an intermediate material, comprising:
[0061] The petroleum coke porous carbon is subjected to a second activation reaction in a fluidized bed; the petroleum coke porous carbon after the activation reaction is subjected to gas phase nano-deposition; and the deposited petroleum coke porous carbon is doped with heteroatoms to obtain the intermediate material.
[0062] The petroleum coke porous carbon is transferred to the fluidized bed cavity, and an inert gas is introduced to exhaust the cavity air. Under a protective atmosphere (i.e., an inert gas atmosphere), a more uniform activation reaction of the petroleum coke porous carbon can be achieved in the fluidized bed to form a more developed pore structure and a higher specific surface area. Chlorosilane is cracked by high-temperature cracking to generate nano-silicon, and nano-silicon is deposited in its pores to increase the specific capacity. By doping with heteroatoms and coating the surface with heteroatoms, the electronic conductivity of the material is improved, thereby improving the rate performance.
[0063] In a preferred embodiment, the second activation reaction comprises: heating the petroleum coke porous carbon to 900-1200°C and introducing an activation gas at a flow rate of 100-500 ml / min for 1-3 hours. The temperature, flow rate and time during the activation reaction at this stage include but are not limited to the above ranges, which are limited to the above ranges. Limiting them to the above ranges is conducive to improving the uniformity of activation, thereby improving the performance of the petroleum coke porous carbon.
[0064] Preferably, the gas phase nano deposition comprises: cooling the petroleum coke porous carbon after the activation reaction to 450-650°C, maintaining the pressure of the fluidized bed chamber at 0.1-0.5Mpa, and introducing a chlorosilane mixed gas at a flow rate of 10-50ml / min for 60-600min. The temperature, pressure, flow rate and time in the gas phase nano deposition process include but are not limited to the above ranges, which are limited to the above ranges. Limiting them to the above ranges is conducive to controlling the growth rate, structure and performance of the deposited layer, thereby optimizing the quality and uniformity of the deposited layer and improving the quality and production efficiency of the product.
[0065] Preferably, the heteroatom doping comprises: heating the deposited petroleum coke porous carbon to 800-1100°C, and introducing heteroatom gas for doping at a flow rate of 10-50 ml / min for 30-300 min. The temperature, flow rate and time during the heteroatom doping process include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving doping efficiency, ensuring the stability and uniformity of material properties, and reducing production costs and improving production efficiency.
[0066] Preferably, the heteroatom gas includes but is not limited to one of hydrides containing nitrogen, boron, phosphorus, and sulfur, oxides containing nitrogen, boron, phosphorus, and sulfur, and ammonia.
[0067] Preferably, the chlorosilane mixed gas is a mixed gas of chlorosilane and nitrogen.
[0068] Preferably, the volume ratio of the chlorosilane to the nitrogen is (1-5):10.
[0069] Preferably, the chlorosilane is one of trichlorosilane, dimethylchlorosilane, hexachlorodisilane, diethyldichlorosilane, dichlorosilane and dichloromethylsilane.
[0070] S3, mixing the intermediate material with the liquid carbon material and transferring the mixture to a rotary kiln for secondary granulation.
[0071] By mixing and granulating the liquid carbon material and the intermediate material, the expansion is reduced, which is beneficial to improving the structural stability, cycle performance and storage performance of the material.
[0072] In a preferred embodiment, the mass ratio of the intermediate material to the liquid carbon material is 100:(5-10). The mass ratio of the intermediate material to the liquid carbon material includes but is not limited to the above range, and limiting it within the above range is beneficial to improving material reaction efficiency, ensuring process stability and improving energy storage efficiency.
[0073] Preferably, the secondary granulation treatment includes: carbonization granulation at a temperature of 500-800° C. for 1-3 hours. The temperature and time during the secondary granulation treatment include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving material quality and optimizing material structure.
[0074] Preferably, the liquid carbon material includes but is not limited to one of liquid asphalt, liquid epoxy resin, liquid polyurethane resin and liquid polyester resin.
[0075] S4, passivating the material after the secondary granulation to obtain a silicon-carbon composite material.
[0076] Depositing a protective film layer, such as amorphous carbon, on the surface of the material after secondary granulation can reduce defects and improve storage performance.
[0077] In a preferred embodiment, the passivation treatment of the secondary granulated material to obtain the silicon-carbon composite material comprises:
[0078] The material after secondary granulation is heated to 1000-1500°C, and a passivation gas is introduced at a flow rate of 10-50 ml / min for passivation for 1-6 hours to obtain the silicon-carbon composite material. The temperature, flow rate and time during the passivation treatment include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the quality of the protective film formed by passivation.
[0079] In a preferred embodiment, the passivation gas includes but is not limited to one of carbon tetrafluoride, carbon difluoride, carbon tetrachloride and carbon dichloride.
[0080] The present application also provides a lithium-ion battery, which includes a positive electrode, a negative electrode, an electrolyte, and a separator arranged between the positive electrode and the negative electrode, and the negative electrode includes a silicon-carbon composite material prepared by the above-mentioned silicon-carbon composite material preparation method provided in the present application.
[0081] The silicon-carbon composite material of the present application is based on petroleum coke, which is modified, and nano-silicon is deposited in its pores, and heteroatom doped, and then granulated and passivated. It uses the high anisotropy and high strength of the petroleum coke matrix to reduce impedance and increase compaction density, and improves the electronic conductivity and coating integrity of the material through heteroatom passivation, and reduces expansion through secondary granulation, improves cycle performance and reduces gas production, and improves rate performance and storage performance.
[0082] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0083] Example 1
[0084] (1) 100 g of petroleum coke, 3 g of polyamide and 10 g of hexanediol diacrylate were mixed uniformly, and then the temperature was raised to 400 ° C for cross-linking reaction for 3 h, and then the temperature was raised to 1350 ° C, carbon dioxide gas was introduced, and activated at a flow rate of 50 ml / min for 300 min to obtain petroleum coke porous carbon;
[0085] (2) The petroleum coke porous carbon is transferred to the fluidized bed chamber, and nitrogen inert gas is introduced to the fluidized bed to exhaust the air in the chamber, and then the temperature is raised to 1100° C. and carbon dioxide activation gas is introduced at a flow rate of 300 ml / min for 2 hours, and then the temperature is lowered to 550° C. and trichlorosilane mixed gas (volume ratio of trichlorosilane: nitrogen = 3:10) is introduced, and the chamber pressure is maintained at 0.3 MPa, and ammonia gas is introduced at a flow rate of 30 ml / min for 300 minutes, and then the temperature is raised to 950° C. and ammonia gas is introduced at a flow rate of 30 ml / min for 120 minutes to obtain an intermediate material;
[0086] (3) 100 g of the intermediate material was mixed evenly with 8 g of liquid asphalt, and transferred to a rotary kiln for carbonization and granulation at 650 °C for 2 h;
[0087] (4) The temperature was then raised to 1250° C., and carbon tetrafluoride gas was introduced, and passivation was performed for 3 h at a flow rate of 30 ml / min to obtain a silicon-carbon composite material.
[0088] Example 2
[0089] (1) 100 g of petroleum coke, 1 g of polycaprolactam and 5 g of triallyl isocyanurate were mixed uniformly, and then the temperature was raised to 300 ° C for cross-linking reaction for 6 h, and then the temperature was raised to 1200 ° C, carbon dioxide gas was introduced, and activated at a flow rate of 10 ml / min for 300 min to obtain petroleum coke porous carbon;
[0090] (2) The petroleum coke porous carbon is transferred to the fluidized bed cavity, and nitrogen inert gas is introduced to the cavity to exhaust the cavity air, and then the temperature is raised to 900°C and water vapor activation gas is introduced at a flow rate of 100 ml / min for 3 hours, and then the temperature is lowered to 450°C and dimethylchlorosilane mixed gas (volume ratio of dimethylchlorosilane: nitrogen = 1:10) is introduced, and the cavity pressure is maintained at 0.5 MPa, and it is introduced at a flow rate of 10 ml / min for 600 minutes, and then the temperature is raised to 800°C and borohydride gas is introduced at a flow rate of 10 ml / min for 300 minutes to obtain an intermediate material;
[0091] (3) 100 g of the intermediate material was mixed evenly with 5 g of liquid epoxy resin, and transferred to a rotary kiln for carbonization and granulation at 500 °C for 3 h;
[0092] (4) The temperature was then raised to 1000° C., and carbon difluoride passivation gas was introduced at a flow rate of 10 ml / min for 6 h to obtain a silicon-carbon composite material.
[0093] Example 3
[0094] (1) 100 g of petroleum coke, 5 g of polyethylene polyamine and 15 g of trimethylolpropane triacrylate were mixed uniformly, and then the temperature was raised to 500 ° C for cross-linking reaction for 1 h, and then the temperature was raised to 1500 ° C, carbon dioxide gas was introduced, and activated at a flow rate of 100 ml / min for 30 min to obtain petroleum coke porous carbon;
[0095] (2) The petroleum coke porous carbon is transferred to the fluidized bed cavity, and nitrogen inert gas is introduced to the fluidized bed to exhaust the cavity air, and then the temperature is raised to 1200° C. and oxygen activation gas is introduced at a flow rate of 500 ml / min for 1 hour, and then the temperature is lowered to 650° C. and a dichloromethylsilane mixed gas (volume ratio of dichloromethylsilane: nitrogen = 5:10) is introduced, and the cavity pressure is maintained at 0.1 MPa, and the flow rate is 50 ml / min for 60 minutes, and then the temperature is raised to 1100° C. and hydrogen sulfide gas is introduced at a flow rate of 10-50 ml / min for 30-300 minutes to obtain an intermediate material;
[0096] (3) 100 g of the intermediate material was mixed evenly with 10 g of liquid polyurethane resin, and the mixture was transferred to a rotary kiln for carbonization and granulation at 800 °C for 1 h;
[0097] (4) The temperature was then raised to 1500° C., and carbon tetrachloride gas was introduced, and passivation was performed at a flow rate of 50 ml / min for 1 h to obtain a silicon-carbon composite material.
[0098] Comparative Example 1
[0099] The difference from Example 1 is that: without adding polyamide and hexanediol diacrylate, 100 g of petroleum coke is directly heated to 400° C. for cross-linking reaction for 3 hours.
[0100] Comparative Example 2
[0101] The difference from Example 1 is that: no secondary granulation is carried out, that is, 100 g of the intermediate material and 8 g of liquid asphalt are not mixed evenly and transferred to a rotary kiln for carbonization and granulation at 650°C for 2 hours. The intermediate material is directly heated to 1250°C, and carbon tetrafluoride gas is introduced and passivated at a flow rate of 30 ml / min for 3 hours to obtain a silicon-carbon composite material.
[0102] Test conditions
[0103] The silicon-carbon composite materials provided in Examples 1 to 3 and Comparative Examples 1 to 2 were tested, and the testing method was as follows:
[0104] (1) SEM test
[0105] Figure 2 is a SEM image of the silicon-carbon composite material prepared in Example 1. Figure 1It can be seen that the silicon-carbon composite material presents a spherical structure with a particle size between 5-10 μm and a uniform size distribution.
[0106] (2) Physical and chemical properties test
[0107] The specific surface area of the silicon-carbon composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was tested with reference to the national standard GB / T 38823-2020 "Silicon Carbon", and the resistivity of each composite material was tested using a four-probe tester; XPS was used to test the coating integrity of the material, and the pore size and pore volume of the porous carbon materials in Examples 1 to 3 and Comparative Examples 1 to 2 were tested respectively. The test results are shown in Table 1.
[0108] (3) Button battery test
[0109] The silicon-carbon composite materials corresponding to Examples 1 to 3 and Comparative Examples 1 to 2 are used as negative electrode materials for lithium-ion batteries. Button batteries are prepared according to the following method: a binder, a conductive agent and a solvent are added to the corresponding silicon-carbon composite materials, stirred to make a slurry, coated on a copper foil, and dried and rolled to obtain a negative electrode sheet; the binder used is LA132, the conductive agent is conductive carbon black (SP), the solvent is N-methylpyrrolidone (NMP), and the ratio of the composite material, SP, LA132, and NMP is 95g:1g:4g:220mL; the electrolyte is LiPF 6 The electrolyte solution has a concentration of 1 mol / L, wherein the solvent is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1; the metal lithium sheet is the counter electrode, and the diaphragm is a polypropylene (PP) film. Each button cell was assembled in an argon-filled glove box, and then the electrochemical performance was tested, specifically on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.005V to 2.0V and a charge and discharge rate of 0.1C. The test results are shown in Table 1.
[0110] The negative electrode sheet of the button cell was also tested for full charge expansion. The specific test process is: the thickness D1 of the negative electrode sheet of the button cell after rolling was tested, and then the full charge thickness D2 of the negative electrode sheet of the button cell was dissected when the button cell was fully charged to 100% state of charge (SOC), and then the expansion rate was calculated (expansion rate = (D1-D2) / D1*100%). The test results are shown in Table 1.
[0111]
[0112] Table 1
[0113] According to Table 1, the specific capacity, initial efficiency and powder resistance of the silicon-carbon composite materials prepared in Examples 1 to 3 of the present application are significantly better than those in Comparative Examples 1 to 2; the reason is that the silicon-carbon composite materials prepared in Examples 1 to 3 improve the electronic conductivity of the material by heteroatom doping and reduce the impedance by granulation, and reduce their expansion.
[0114] (4) Soft pack performance test
[0115] The silicon-carbon composite materials corresponding to Examples 1 to 3 and Comparative Examples 1 to 2 were doped with 90% artificial graphite as negative electrode materials (i.e., negative electrode plates) and positive electrode ternary materials (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 ), electrolyte and diaphragm are assembled into a 5Ah soft pack battery; the diaphragm is celegard 2400, the electrolyte is LiPF 6 Solution (solvent is a mixed solution of EC and DEC with a volume ratio of 1:1, LiPF 6 The concentration of the mixture is 1.3 mol / L) to prepare a soft-pack battery.
[0116] A. The test conditions for the cycle performance test are:
[0117] The charge and discharge voltage range is 2.5-4.2V, the temperature is 25±3.0℃, the charge and discharge rate is 1.0C / 1.0C, and the cycle number is 500. The test results are shown in Table 2.
[0118] B. The test conditions for rate test are:
[0119] HPPC test of the test material, after 3C pulse for 10S, the charging DCR at different SOC (95%, 90%, 80%, 70%, 50%, 30%, 20%, 10%, 5%) was tested. The test results are shown in Table 2.
[0120]
[0121] Table 2
[0122] It can be seen from Table 2 that the rate and cycle performance of the soft-pack lithium-ion battery prepared using the silicon-carbon composite materials provided in Examples 1 to 3 are significantly better than those in Comparative Examples 1 to 2; the reason may be that: the silicon-carbon composite materials provided in Examples 1 to 3 have low powder resistivity, which reduces the DC internal resistance (DCR); at the same time, the silicon-carbon composite materials provided in Examples 1 to 3 have a high specific surface area, which improves the liquid retention performance of the material and improves the cycle performance.
[0123] From the above description, it can be seen that the silicon-carbon composite material prepared by the method for preparing the silicon-carbon composite material provided in the embodiment of the present application has the following technical effects:
[0124] (1) The preparation method of the silicon-carbon composite material provided in the present application comprises carbonizing a mixture of petroleum coke, a pore-forming agent and a cross-linking agent, and utilizing the nano- and micro-pores left after the carbonization of the pore-forming agent to form pores, and utilizing the cross-linking agent to connect the carbon obtained after the carbonization of the petroleum coke, thereby improving the strength of the porous carbon itself, improving its compressive resistance and reducing its expansion.
[0125] (2) The preparation method of the silicon-carbon composite material provided in the present application prepares porous carbon by high-temperature sintering under modified gas conditions, which has the advantages of large pore volume, few carbon-based material defects, and high compaction density. In addition, the selected petroleum coke raw material has a wide source, low cost, and good consistency.
[0126] (3) The preparation method of the silicon-carbon composite material provided in the present application uses high-temperature pyrolysis to crack chlorosilane to generate nano-silicon, which is deposited in porous carbon to increase the specific capacity, and heteroatoms are coated on its surface to increase the electronic conductivity of the material and improve the rate performance.
[0127] (4) The preparation method of the silicon-carbon composite material provided in the present application uses a liquid carbon material to mix and granulate the silicon-carbon precursor to reduce expansion, and deposits amorphous carbon on its surface to reduce defects and improve storage performance.
[0128] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
[0129] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a silicon-carbon composite material, characterized in that: The method comprises: Preparation of petroleum coke porous carbon; Under a protective atmosphere, vapor-depositing and doping the petroleum coke porous carbon in a fluidized bed to obtain an intermediate material; The intermediate material is mixed with the liquid carbon material and then transferred to a rotary kiln for secondary granulation treatment; The material after the secondary granulation is passivated to obtain a silicon-carbon composite material.
2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing petroleum coke porous carbon comprises: Mixing petroleum coke, a pore-forming agent and a cross-linking agent to obtain a mixed material; performing a cross-linking reaction on the mixed material; The mixed material after the cross-linking reaction is subjected to a first activation reaction to obtain the petroleum coke porous carbon.
3. The method for preparing the silicon-carbon composite material according to claim 2, characterized in that: The mass ratio of the petroleum coke, the pore former and the cross-linking agent is 100:(1-5):(5-15); The cross-linking reaction comprises: heating the mixed material to 300-500° C. and performing a cross-linking reaction for 1-6 hours; The first activation reaction comprises: heating the mixed material after the cross-linking reaction to 1200-1500° C. and introducing carbon dioxide gas at a flow rate of 10-100 ml / min for activation for 30-300 minutes.
4. The method for preparing the silicon-carbon composite material according to claim 2 or 3, characterized in that: The method comprises using any one or more combinations of the following: The pore former is any one of polyamide, polycaprolactam, polyethylene polyamine, polyethylene amine and polycaprolactam; or The crosslinking agent is any one of hexanediol diacrylate, triallyl isocyanurate, trimethylolpropane triacrylate and pentaerythritol triacrylate.
5. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The step of vapor deposition doping the petroleum coke porous carbon in a fluidized bed to obtain an intermediate material comprises: performing a second activation reaction on the petroleum coke porous carbon in a fluidized bed; The petroleum coke porous carbon after activation reaction is subjected to gas phase nano-deposition; The deposited petroleum coke porous carbon is doped with heteroatoms to obtain the intermediate material.
6. The method for preparing the silicon-carbon composite material according to claim 5, characterized in that: The second activation reaction comprises: heating the petroleum coke porous carbon to 900-1200° C. and introducing activation gas at a flow rate of 100-500 ml / min for 1-3 hours; The gas phase nano deposition comprises: cooling the petroleum coke porous carbon after the activation reaction to 450-650° C., maintaining the pressure of the fluidized bed chamber at 0.1-0.5 MPa, and introducing a chlorosilane mixed gas at a flow rate of 10-50 ml / min for deposition for 60-600 min; The heteroatom doping comprises: heating the deposited petroleum coke porous carbon to 800-1100° C., and introducing heteroatom gas for doping at a flow rate of 10-50 ml / min for 30-300 min; The heteroatom gas is one of hydrides containing nitrogen, boron, phosphorus, and sulfur, oxides containing nitrogen, boron, phosphorus, and sulfur, and ammonia; The chlorosilane mixed gas is a mixed gas of chlorosilane and nitrogen, and the volume ratio of the chlorosilane to the nitrogen is (1-5):10; The chlorosilane is one of trichlorosilane, dimethylchlorosilane, hexachlorodisilane, diethyldichlorosilane, dichlorosilane and dichloromethylsilane.
7. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The mass ratio of the intermediate material to the liquid carbon material is 100:(5-10); The secondary granulation treatment includes: carbonization granulation at a temperature of 500 to 800° C. for 1 to 3 hours; The liquid carbon material is one of liquid asphalt, liquid epoxy resin, liquid polyurethane resin and liquid polyester resin.
8. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The passivation treatment of the secondary granulated material to obtain the silicon-carbon composite material comprises: The material after secondary granulation is heated to 1000-1500° C., and a passivation gas is introduced at a flow rate of 10-50 ml / min for passivation for 1-6 hours to obtain the silicon-carbon composite material.
9. The method for preparing the silicon-carbon composite material according to claim 8, characterized in that: The passivation gas is one of carbon tetrafluoride, carbon difluoride, carbon tetrachloride and carbon dichloride.
10. A lithium ion battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode, characterized in that: The negative electrode comprises a silicon-carbon composite material prepared by the method for preparing a silicon-carbon composite material according to any one of claims 1 to 9.
Citation Information
Cited By
Preparation method of pitch-based porous carbon for high-performance silicon carbon
CN120922872A
A method for preparing pitch-based porous carbon for high-performance silicon-carbon applications
CN120922872B
Heteroatom-doped calcined coke material as well as preparation method and application thereof
CN120943240A